ESTIMATION OF TECHNICAL EFFICIENCY OF RED CHILI FARMING ON JAVA AND OUTSIDE JAVA, INDONESIA: A STOCHASTIC FRONTIER PRODUCTION APPROACH - Nurmalita, Ika; Fariyanti, Anna; Novianti, Tanti (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
The supply of red chili in various regions in Indonesia still relies on production from Java. Different uses of production factors are insufficient to overcome production gap between Java and other regions, so measuring other factors is required. This study aims to analyze the factors affecting red chili production, identify the technical efficiency level of red chili, and analyze factors affecting the technical efficiency of red chili in Java and outside Java. This study used data from the 2013 Agricultural Census (ST2013) and the 2014 Horticultural Crop Farming Household Survey from the Central Statistics Agency (BPS). The SFA (Stochastic Frontier Analysis) method was applied to estimate the technical efficiency levels and the factors influencing it. The results revealed that factors such as seeds, harvest area, N-fertilizer, K-fertilizer, manure, pesticides, and labor affect red chili production in Java. Outside Java, the influencing factors are seeds, harvest area, N-fertilizer, P-fertilizer, manure, pesticides, and labor. The technical efficiency of red chili in Java (0.640) is lower than outside Java (0.691), indicating outside Java more technically efficient than Java. The significant factors affecting the technical efficiency of red chili farming in Java include education, participation in farmer groups, participation in cooperatives, land type, growing season, subsidies, technology, certified seeds, and access to credit. Conversely, outside Java, only cooperative participation, land type, growing season, and technology have a significant impact. Assistance in using subsidized inputs and access to credit in Java and the development of cooperative institutions outside Java are policies that can be taken.